What Lies under the Chair! A Study in Ancient Egyptian Private Tomb Scenes, Part II: Objects - Mahran, Heba.
Following on the rst part of the study, which dealt with scenes of animals under the chairs of nobles and members of their families, the main interest of the second part is the various objects represented under those chairs. The present article seeks to categorize types of objects and analyze the reason behind their representation under the chairs. Over fty private tombs and reliefs supported by similar scenes on stelae were examined and analyzed. The objects that appeared under chairs are chests and boxes, mirrors, vessels, cosmetics, scribal equipment, ewers and basins, owers, and miscellaneous objects such as bowls, sandals, headrests, and the senet game. The study revealed that placing objects under the chair began during the Sixth Dynasty. Chests and boxes were preferred under the chairs during that period while vessels were preferred during the New Kingdom. The existence of objects under the chair in certain tombs does not exclude animals from being represented in the same tomb occupying their own scenes or being represented next to objects. As with animals, scenes of objects under the chairs were rare during the Middle Kingdom. The study also noted explicitly that each of these objects was placed under the chair either to serve personal purposes in the afterlife as they did in real life, indicating the deceased’s occupation, or to serve in some religious ceremonies. doi: http://dx.doi.org/10.5913/jarce.52.2016.a002